Biochemical and Metabolic Aspects of Platelet Dysfunction in Chronic Myeloproliferative Disorders - Pareti, F I; Gugliotta, L; Mannucci, L; Guarini, A; Mannucci, P M (Thrombosis and Haemostasis, 1982)
Fifty-two patients with chronic myeloproliferative disorders (13 with polycythemia vera; 23 with primary thrombocythemia; 6 with myelofibrosis and 10 with chronic granulocytic leukemia) had low platelet levels of adenine nucleotides and serotonin and abnormal uptake and storage of the amine. The storage pool deficiency was confined to the substances contained in the platelet dense bodies, because α-granule and lysosome markers were present in normal amounts. In chronic granulocytic leukemia the storage defect was usually less marked but was accompanied by a decreased formation of thromboxane B2 and normal platelet aggregation in response to arachidonic acid. There was no clearcut relationship of these biochemical abnormalities to prolongation of bleeding time or to thrombotic and hemorrhagic symptoms. The defect was still present in 15 patients after treatment had returned the cell counts to the normal range. Normal levels of 5HT and adenine nucleotides were observed in 8 patients whose platelet counts were high after splenectomy for non-hematological reasons. These findings suggest that biochemical abnormalities are related to the presence in the bone marrow of abnormal clones, resulting in the production of defective platelets.
Keywords: Thrombocytopathy; Storage pool deficiency; Platelet qualitative defects; Platelet dense bodies; Serotonin metabolism